Severe Acute Respiratory Syndrome Coronavirus 2 Neutralization After Messenger RNA Vaccination and Variant Breakthrough Infection. (7th May 2022) - Gaebler, Christian; DaSilva, Justin; Bednarski, Eva; Muecksch, Frauke; Schmidt, Fabian; Weisblum, Yiska; Millard, Katrina G; Turroja, Martina; Cho, Alice; Wang, Zijun; Caskey, Marina; Nussenzweig, Michel C; et al.
Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 variants that have greater transmissibility and resistance to neutralizing antibodies has increased the incidence of breakthrough infections. We show that breakthrough infection increases neutralizing antibody titers to varying degrees depending on the nature of the breakthrough variant and the number of vaccine doses previously administered. Omicron breakthrough infection resulted in neutralizing antibody titers that were the highest across all groups, particularly against Omicron.